Evaluation of Stress Tolerance and Fermentation Performance in Commercial Yeast Strains for Industrial Applications - Anqi Chen; Qiqi Si; Qingyun Xu; Chenwei Pan; Tianzhi Qu; Jian Chen (Foods)
This study evaluates the stress tolerance and metabolic adaptability of twelve yeast strains, including eleven commercial strains from Wyeast Laboratories and one prototrophic laboratory strain, under industrially relevant conditions. Yeast strains were assessed for their fermentation performance and stress responses under glucose limitation, osmotic stress, acid stress, elevated ethanol concentrations, and temperature fluctuations. Results revealed significant variability in glucose consumption, ethanol production, and stress tolerance across strains. ACY34 and ACY84 demonstrated the highest fermentation efficiency, while ACY19 exhibited exceptional stress resilience, excelling under multiple stress conditions such as osmotic and ethanol stress. The findings highlight strain-specific performance, with some strains suited for high-yield fermentation and others excelling under challenging environmental conditions. These results provide critical insights for selecting and optimizing yeast strains tailored to specific industrial fermentation processes, contributing to improved productivity and product quality in food and beverage production.